Influência da pós-carga sobre a taxa de variação da tensão desenvolvida (dT/dt). Estudo em músculo cardíaco isolado. - Okoshi, M. P.; Ferreira Tucci, P. J.; Okoshi, K.; Padovani, C. R.; Cicogna, A. C. (My University, 1995)
PURPOSE: To evaluate the effects of afterload on peak rate of tension rise (dT/dt) in the isolated muscle. METHODS: Left ventricular papillary muscles from Wistar rats were studied in isometric and isotonic afterloaded contractions. Muscles were analised in Krebs-Henseleit solution with calcium concentration of 2.52mM at 28 degrees C. The resting muscle length (preload) was maintained constant. The peak isometric developed tension (DT) and dT/dt were measured during increases of afterload (25, 50, 75 and 100% from DT). RESULTS: A rise in afterload corresponding to 50, 75 and 100% of DT, did not cause an increase in dT/dt values (p > 0.05). The dT/dt value decreased (p < 0.05) when afterload was changed from 75% to 25% of DT. CONCLUSION: The data suggest that an increase in the afterload from 50% of the DT did not promote changes in the dT/dt.
Influence of afterload on the rate of variation of developed pressure (dT/dt). Study in isolated cardiac muscle
Keywords: animal; heart contraction; heart output; heart papillary muscle; male; muscle isometric contraction; physiology; rat; Wistar rat; Animals; Cardiac Output; Isometric Contraction; Male; Myocardial Contraction; Papillary Muscles; Rats; Rats, Wistar